ADRB2 and ACE Gene Polymorphisms in COPD Susceptibility - Ganbold, Chimedlkhamsuren; Jamyansuren, Jambaldorj; Puntsag, Odonchimeg; Batjargal, Ochbadrakh; Dashtseren, Ichinnorov; Jav, Sarantuya (Central Asian Journal of Medical Sciences, 2016)
Objectives: Recent studies have established that rs1042713 and rs1042714 polymorphisms in the ADRB2 and rs4646994 in the ACE gene may have an influence on chronic obstructive pulmonary disease (COPD) development and its severity. The aim of this study was to investigate the association of ACE and ADRB2 gene polymorphisms with COPD. Methods: 100 patients with COPD and 100 healthy volunteers were randomly involved in this case-control study. The gene polymorphisms were identified by polymerase chain reaction (PCR) and restriction fragment length polymorphism analysis. Results: No significant differences were observed for allele and genotype frequencies of the rs4646994 polymorphism in the ACE gene between case and control groups (p > 0.05). Genotype frequencies of Gly/Gly16 (OR = 2.31, 95% CI = 1.23-4.32, p = 0.027) and Gln/Gln27 (OR = 2.04, 95% CI = 1.14-3.63, p = 0.044) of the ADRB2 gene were more prevalent in COPD patients than the controls. Also, the proportion of the Gly16+Gln27 haplotype was statistically different between both groups (OR = 2.62, 95% CI: 1.65-4.15, p<0.001) Conclusion: There is no relation between the rs4646994 polymorphism in the ACE gene and COPD, but the homozygote Gly/Gly16 and Gln/Gln27 variations of the ADRB2 gene may increase the carrier’s susceptibility to the development of COPD.